Outcomes following surgical versus endovascular treatment of spinal dural arteriovenous fistula: a systematic review and meta-analysis. Issue 10 (29th May 2019) - Goyal, Anshit; Cesare, Joseph; Lu, Victor M; Alvi, Mohammed Ali; Kerezoudis, Panagiotis; Brinjikji, Waleed; Nasr, Deena; Lanzino, Guiseppe; Bydon, Mohamad
Abstract : Although surgical resection is associated with a complete cure in most cases of spinal dural arteriovenous fistulas (SDAVF), there has been an increasing trend towards embolisation. We performed a systematic review and meta-analysis comparing surgical resection with endovascular treatment in terms of success of treatment, rate of recurrence and complications. A literature search was conducted using Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Strength of evidence was assessed using the Grading of Recommendations Assessment, Development and Evaluation Working Group system. Surgical outcomes such as initial treatment failure, late recurrence, neurological improvement and complications were compared between the two approaches. We included 57 studies with 2029 patients, of which 32 studies with 1341 patients directly compared surgery (n=590) and embolisation (n=751). Surgery was found to be associated with significantly lower odds of initial treatment failure (OR: 0.15, 95% CI 0.09 to 0.24, I 2 0%, p<0.001) and late recurrence (OR 0.18, 95% CI 0.09 to 0.39, I 2 0%, p<0.001). The odds of neurological improvement following surgery were also significantly higher compared with embolisation alone (OR: 2.73, CI:1.67 to 4.48, I 2 :49.5%, p<0.001). No difference in complication rates was observed between the two approaches (OR 1.78, 95% CI 0.97 to 3.26, I 2 0%, p=0.063). Onyx was associated with significantly higher odds of initial failure/late recurrence as compared with n-butyl 2-cyanoacrylate (OR: 3.87, CI: 1.73 to 8.68, I 2 :0%, p<0.001). Surgery may be associated with superior outcomes for SDAVFs in comparison to endovascular occlusion. Newer embolisation agents like Onyx have not conferred a significant improvement in occlusion rate.